Book Reviews. (1st March 2014) - Courtois, Cédric; Given, Jock; Picard, Robert G.
The Social Use of Media, Helena Bilandzic, Geoffroy Patriarche and Paul Traudt (eds) (2012) Bristol/Chicago: Intellect, 202 pp., ISBN: 9781841505121, p/bk, £25Shut-Off: the Canadian Digital Television Transition, Gregory Taylor (2013) Montreal: McGill-Queen's University Press, 232 pp., ISBN: 9780773540491, p/bk, $29.95Private Television in Western Europe: Content, Markets, Policies, Karen Donders, Caroline Pauwels and Jan Loisen (eds) (2013) Basingstoke: Palgrave Macmillan, 296 pp., ISBN: 9782248027543, h/bk, £55